Aprendizagem histórica de jovens estudantes no envolvimento com o jogo eletrônico : um estudo da relação intersubjetiva entre consciência histórica e cultura histórica - Freitas, Rafael Reinaldo (2017)
This research aims to understand the historical learning trought the electronic game based on the ideas presented by students in the context of schooling. Inserted in the perspectives of the field of Historical Education, we tried to understand the historical learning from “cognição histórica situada” in a specific approach based on the ideas mobilized by such subjects taking as a theoretical matrix the historical consciousness in Jörn Rüsen. For that, a theoretical contextualization is presented with the aim of distinguishing other works that investigated the electronic games, taking incentive of the qualitative, non descriptive approach. To think of historical learning from the science of reference is possible in a dialogue with historical consciousness, adding the empirical consideration of the place of intersubjectivity in the process of subjectivation of historical knowledge according to Fronza. The intersubjective relation can be measured when the aestheticization of the past in the electronic game is clear, therefore, it is problematized such languages with theoretical considerations of Jesper Jull and Katie Salem & Zimmerman. Finally, an investigative tool with objective and open questions was developed and applied, considering the need to investigate how young students relate to videogame, historical narrative and finally how they see the historical learning in this language. The interpretation of this questionnaire resulted in the reduction of data in tables, as proposed by Flick, whose classification and classification criteria come from the philosophy of history, extended by the experience of researchers of Historical Education. After this, strategies were mobilized in arguments that address the question of metahistory, namely, historical truth, intentionality, objectivity and subjectivity.